CORRELATION OF ARCHEAN ROCKS FROM THE KOLA SUPERDEEP BOREHOLE AND THEIR ANALOGUES FROM THE SURFACE: EVIDENCE FROM STRUCTURAL-PETROLOGICAL, PETROPHYSICAL, AND NEUTRON DIFFRACTION DATA - Lobanov K.V.; Kazansky V.I.; Kuznetsov A.V.; Zharikov A.V.; Nikitin A.N.; Ivankina T.I.; Zamyatina N.V. (My University, 2002)
The paper reports the results of complex studies of core samples of Archean rocks from the Kola Superdeep Borehole and analogues of these rocks collected at the surface. The analogy of these rocks is justified by the determined quantitative proportions of minerals, their microprobe analyses, and analysis of mineral assemblages using microstructural, petrophysical, and neutron diffraction methods. Particular attention is focused on the anisotropy of the rocks and its description based on a variety of techniques. Consequently, the first petrological, structural, and petrophysical characteristics are obtained for the framework that composes deep-seated zones of the ancient continental crust and in which later processes could proceed. The paper is the first to present the results of complex analysis of different types of information on the three-dimensional geological space. The first data are also reported on the changes in the porosity and permeability of the rocks composing the core when it is recovered from significant depths.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей